2008
DOI: 10.1139/h08-068
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins 27 and 70 regulating angiotensin II-induced NF-κB: a possible connection to blood pressure control?

Abstract: Heat shock proteins (HSPs) are critical for cell survival and have several mechanisms of action. HSPs regulate protein folding, suppress apoptosis, and regulate anti-oxidative activity. In addition, HSPs are involved in the regulation of the pro-inflammatory transcription factor nuclear factor (NF)-kappaB. When angiotensin (Ang) II is infused into rats, there is a significant increase in systolic blood pressure, and NF-kappaB is activated in the heart. If rats are heat shocked to induce the heat shock response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Accumulating evidence suggests that the protective (antiinflammatory) role of Hsp70 is mediated through downregulation of NF-κB, since NF-κB activation and translocation into the nucleus promotes elevated proinflammatory mediators (14,(16)(17)(18)(19)(20)(21)41,50,72,73). Consistent with this notion, we and others have demonstrated that overexpression of Hsp70 protein blocks nuclear translocation of NF-κB and thereby reduces proinflammatory mediator production (19)(20)(21)50).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Accumulating evidence suggests that the protective (antiinflammatory) role of Hsp70 is mediated through downregulation of NF-κB, since NF-κB activation and translocation into the nucleus promotes elevated proinflammatory mediators (14,(16)(17)(18)(19)(20)(21)41,50,72,73). Consistent with this notion, we and others have demonstrated that overexpression of Hsp70 protein blocks nuclear translocation of NF-κB and thereby reduces proinflammatory mediator production (19)(20)(21)50).…”
Section: Discussionsupporting
confidence: 75%
“…Since circulating levels of Gln were significantly reduced in children with SMA (see Figure 5A), and Gln improves clinical outcomes in acute illness and injury through increasing Hsp70 expression, an event that attenuates NF-κB translocation to nucleus (28,41,54), we determined whether the addition of Gln could overcome PfHz-induced against severe disease. Since our studies are conducted in a holoendemic P. falciparum transmission region of western Kenya, nearly all the children get repeated episodes of malaria prior to developing naturally acquired immunity.…”
Section: Effect Of Glutamine On Hemozoininduced Suppression Of Hsp70mentioning
confidence: 99%
“…Interestingly, Hsp70 is involved in the regulation of Ang IIinduced NF-κB. In agreement, HSPs were related to the proinflammatory transcription factor NF-κB (Voegeli et al 2008).…”
Section: Effect Of Hsp70 On Pro-inflammatory Activation Of Epithelialmentioning
confidence: 56%
“…However, despite the substantial evidence that extracelluar HSP27 can act as an anti-inflammatory, the role of extracellular HSP27 in the regulation of NF-κB signaling is unclear. Several studies have examined the affect of intracellular HSP27 on NF-κB; however, these indeterminate results are mainly in cell types that have not been demonstrated to secrete HSP27, such as smooth muscle cells (Parcellier et al 2003;Voegeli et al 2008). Therefore, in the current study, we sought to examine whether extracellular HSP27 could modulate NF-κB signaling in macrophages.…”
Section: Samira Salari and Tara Seibert Contributed Equally To This Workmentioning
confidence: 99%